Kombinasi Metode SAW dan WASPAS dalam Menentukan Mekanik Terbaik - Surianto, Dedi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The problem that occurs in the Arena workshop is that the process of selecting the best mechanics still uses conventional methods, namely by looking at the performance of the entire mechanic without calculating the values ​​or weights of each selected mechanic criteria. Of course, this method makes the selection process less accurate and less fast. Therefore, to facilitate the Arena Workshop in the process of selecting the best mechanic, a system is needed that can select and determine decisions quickly and accurately. A reliable system is the Decision Support System. The decision support system uses the SAW and WASPAS methods. The combination of the SAW method is carried out to find the matrix normalization value, and the WASPAS method is used to find the best mechanic ranking. Based on the test results with 10 samples of mechanic names, it was found that the mechanic with the A4 alternative managed to get the highest ranking value, which was 49.054 and the lowest was A10 with a value of 30.75.